FREUDIAN DEFENSE MECHANISMS OF THE CHARACTER KENNA IN THE NOVEL REMINDERS OF HIM BY COLLEEN HOOVER - Nur Haera Aradjim; Magdalena Baga; Adriansyah A Katili (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2025)
The novel Reminders of Him depicts the inner conflicts of the main character, Kenna, caused by her past experiences and mistakes, and displays her responses in facing these inner conflicts. This research is important to enrich knowledge about psychological defense mechanisms in facing inner conflicts. Thus, this study aims to analyze Kenna's response to her inner conflict in the novel Reminders of Him using Sigmund Freud's psychoanalytic theory. This study uses a qualitative method with a literary structural and psychological approach. This study shows that the defense mechanisms of rationalization, denial, suppression, repression, and sublimation are the responses shown by Kenna in facing her inner conflicts. This analysis shows that past experiences and mistakes are able to trigger ego defense mechanisms that hinder personal growth, but encounters with positive figures ultimately have a positive impact, such as the use of sublimation, emphasizing the role of literature as a means to have an understanding of the complexity of human psychological development and strengthening.